(untitled) (Boletín Semillero de Investigación en Familia, 2025)
Adverse health events not only affect patients but also the professionals involved, known as second victims. These individuals may experience physical (insomnia, fatigue), emotional (guilt, fear, anxiety), and psychological (post-traumatic stress symptoms) effects, which affect their performance and well-being. At work, this can translate into absenteeism, sick leave, or even leaving the profession. This situation also impacts institutions, weakening organizational culture and affecting the quality of service. Caring for those who care is not only an ethical duty, but also a guarantee of safe and humane care for patients.